Measurement of the Constructs of Health Belief Model related to Self-care during Pregnancy in Women Referred to South Tehran Health Network - Yalda Soleiman Ekhtiari; Fereshteh Majlessi; Abbas Rahimi Foroushani (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Self-care activities during pregnancy can be effective in reducing adverse pregnancy outcomes. Health Belief Model (HBM) is one of the most applicable models in educational need assessment for planning and implementation of educational interventions. The purpose of this study was to measurement of the constructs of HBM related to self-care during pregnancy in women referred to South Tehran health network. Materials and Methods: In this cross-sectional study 270 pregnant women who referred to health centers of South Tehran Health Networks participated. Demographic, knowledge and attitude questionnaires based on constructs of HBM was used to measure the status of knowledge and attitude of women. Data were analyzed using statistical software SPSS18. Results: Results showed that 92.2% of women had the knowledge scores in good level. The scores of perceived severity, perceived self-efficacy and cues to action were in good level in almost of women but almost of women obtained weak point in perceived susceptibility, perceived benefits and barriers Conclusion: HBM can be used as an appropriate tool for assessment the status of pregnant women in the field of self-care behaviors during pregnancy and planning and implementation of educational interventions.